Efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors combined with chemoradiotherapy for locally advanced rectal cancer: a systematic review and meta-analysis - Yu, Jiaojiao; Wang, Zhijing; Li, Mingxu; Zhu, Hua; Tang, Xiaoxia; Luan, Ke; Zhi, Yinhuan; Yin, Shan; Su, Yuanqi; Long, Jingyan; He, Qubo; Quan, Jieru; et al. (Frontiers in Pharmacology, 2025)
BackgroundThe objective of this meta-analysis was to assess the effectiveness and safety of neoadjuvant PD-1/L1 inhibitors plus chemoradiotherapy(CRT) for locally advanced rectal cancer (LARC).Materials and MethodsDatabases including PubMed, Embase, Cochrane Library and Web of Science were examined for pertinent studies. Meta-analyses were conducted on pathological complete response (pCR), clinical complete response (cCR), major pathologic response (MPR), sphincter-sparing surgery (SSS), R0 resection, surgery rate, Grade≥3 adverse events (AEs), and 3-year disease-free survival (DFS).ResultsThe combined percentages of pCR, cCR, MPR, SSS, R0 resection rate, surgery rate, and 3-year DFS were 30.8%, 20.8%, 57.6%, 70.3%, 75.8%, 83.5%, and 76%, respectively. Grade ≥3 AEs manifested in 33.9% of cases. In subgroup analysis, mismatch repair-deficient (dMMR) or microsatellite instability-high (MSI-H) showed 50.2% pCR and 64.7% MPR. Long-course radiotherapy (LCRT) and short-course radiotherapy (SCRT) had 39.1% and 27.1% pCR rates. The contemporaneous and sequential immuno-chemoradiotherapy subgroups had 30.8% and 30.1% pCR rates. These rates matched the 33.1% and 30% pCR rates for the PD-L1 and PD-1 inhibitor subgroups. The PD-L1 and PD-1 inhibitor categories had 20.6% and 38.8% rate of Grade ≥3AEs.ConclusionNeoadjuvant PD-1/PD-L1 inhibitors plus CRT have demonstrated favourable response rates and tolerable toxicity profiles for LARC.Systematic Review RegistrationPROSPERO (CRD42024569289) https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024569289.